Effect of Head and Face Massage on Agitation in Elderly Alzheimer's Disease Patients - Saeid Keshavarz; Tayebeh Mirzaei; Ali Ravari (Mashhad University of Medical Sciences, 2018)
Background: Management of agitation in Alzheimer's patients with non-invasive treatment methods, such as massage therapy, is of paramount importance. Aim: This study was conducted to determine the effects of head and face massage on agitation in elderly Alzheimer's patients living in nursing homes in Yazd, Iran. Method: This randomized controlled clinical trial was conducted on two groups (n=35 in each group) from 26 September to 5 October 2016. For the patients in the intervention group, massage therapy was performed using the effleurage and compression techniques, and no intervention was implemented in the control group. The usual way to control the symptoms of agitation was physical restraint. The Cohen-Mansﬁeld Agitation Inventory (CMAI) was used to measure the agitation level. The data were analyzed by performing Wilcoxon and Mann-Whitney tests in SPSS, version 18. Results: The mean ages of the intervention and control groups were 82.2±10.6 and 81.5±9.6 years, respectively. The mean scores of agitation in the intervention and control groups decreased from 77.2±14.4 and 82.1±17.3 before the intervention to 49.7±6.0 and 80.8±18.3 after the intervention, respectively. The results showed a significant difference between the two groups after the intervention (P